Síntese verde e caracterização de nanopartículas de ferro valência zero utilizando diferentes extratos de plantas - Bertoleti, Luana Malaquias (2023)
Water is a vital natural resource for plants, animals, and humans, but only 2.5% of the water on earth is fresh. Population growth and industrial development are causing environmental pollution and threatening human health. Nanoparticles are being used effectively to remove impurities from water due to their specific properties. However, the conventional production of nanoparticles faces challenges such as agglomeration, waste generation, and high costs. Green synthesis of nanoparticles, which is more sustainable and environmentally friendly, is presented as a solution to these limitations. The objective of this work was to produce zero-valent iron nanoparticles from plant extracts, as well as to evaluate their potential for discoloration of the reactive blue dye 19. Eighteen plant extracts were tested and six were selected based on their yield. The nanoparticle samples produced were characterized by X-ray diffraction, scanning electron microscopy, energy dispersive spectroscopy, and Fourier transform infrared spectroscopy. Both analyses demonstrated that the 6 extracts produced nanoparticles with a similar profile, presenting characteristics of zero valence iron nanoparticles. X-ray diffractograms showed a characteristic peak of zero valence iron at 44° in 2θ. The infrared spectra showed absorption bands in the 815 and 550 cm-1 regions commonly attributed to iron nanoparticles. Scanning electron microscopy showed the profile of particles of different sizes and shapes. The energy dispersive spectroscopy analysis showed that the majority of elemental composition was carbon, followed by oxygen and iron. The study of the efficiency of decolorization of the reactive blue dye 19 was carried out by adding nanoparticles of zero-valent iron in the dye solution stirred in an orbital shaker, to evaluate the efficiency of degradation measured from spectrophotometric readings at the maximum ʎ of the dye. After the previous study of the reactivity of the 6 samples of nanoparticles, a complete factorial design was carried out to evaluate the influence of the variable’s pH and concentration of nanoparticles in the discoloration process. Furthermore, this study was used to select the best condition for studying the discoloration kinetics and obtaining a prediction model. The nanoparticles produced from moringa extract showed a greater capacity for discoloration (40%) than the reactive blue dye 19. The ideal conditions for reactivity were obtained with a concentration of nanoparticles of 1.5 g/L and pH 8. In general, the results indicated that the nanoparticles obtained through green synthesis presented a typical structure and morphology in the form of agglomerates, with exposure of irregular particles on the surface and reactivity for degradation of the reactive blue dye 19.